M.I.C.E. Tourism as a Human Resources Management Tool (Aplication Study AIESEC) - Pacáková, Kateřina (2015)
The thesis describes characteristics of MICE tourism in general and in the Czech Republic. It also observes usage and process of preparation of MICE products in student organizations, namely in AIESEC Czech Republic and Student Union CTU, and presents a general eight aspect scheme for organizing such events to ensure their contribution to human resources management.